Portraits of whiteness: examining fragility and the practices that perpetuate and disrupt whiteness among white pre-service teachers - Bell, Thomas H., III, author; Muñoz, Susana, advisor; Basile, Vincent, advisor; Bimper, Albert, committee member; Birmingham, Daniel, committee member (Colorado State University. Libraries, 2019)
National data indicated approximately 80 percent of the teaching force is white while the student population continues to become increasingly racially diverse. Teacher education programs continue to graduate and recommend for licensure a disproportionate number of white teachers. Research indicates overwhelmingly pre-service teachers suffer from a collective experience enculturating their miseducation as it relates to deconstructing and disrupting whiteness. Using Critical Race Theory and Critical whiteness Studies, this study utilized portraiture and narrative inquiry to understand how seven white pre-service teachers are engaging or not engaging with their whiteness. In particular the portraits (APPENDIX A) enhance a deeper understanding of the factors contributing to the participant's ability and willingness to engage on race and disrupt whiteness. Through thematic analysis of the portraits, five themes emerged which provide a deeper understanding of the factors that contribute to the willingness to disrupt or challenge whiteness in the context of teaching. These themes also discuss the miseducation of these seven participants related to their ability to engage in disrupt whiteness during their experience in a teacher preparation program.
Keywords: teacher education; disruption; whiteness